Study on the Chemical Characterization and Hypolipidemic Function of Nelumbo nucifera Based on Its Flavonoid Components - Leyi Yang; Chang Zhou; Rong Huang; Yuan Cai; Bin Liu; Mimi Yu; Yanyan Jiang (Molecules)
Nelumbo nucifera has great value and development prospects in hypolipidemic applications. In this study, we comprehensively screened out multi–index components relevant to the quality of N. nucifera based on the hypolipidemic function of the flavonoid fraction of N. nucifera (FFN) combined with chemical characterizations. Firstly, in vitro antioxidant and cell experiments evaluated the hypolipidemic function of the FFN. Secondly, the chemical compositions of N. nucifera were identified by UPLS–MSn technology. Then, the multi–index flavonoid components (rutin, hyperoside, isoquercitrin, quercetin–3–O–β–D–glucuronide, astragalin, and quercetin) were determined using a quantitative fingerprint combined with multivariate statistical data analysis. Finally, the quality of N. nucifera was scientifically evaluated by multi–index quantitative analysis combined with multivariate statistical data analysis, which was used to study the relationship between the content of flavonoid components and the overall quality. The above–mentioned research lays a material foundation for improving the quality standards of N. nucifera, providing a basis for developing functional foods to improve dyslipidemia.